ADVANTAGES OF USING THE METHOD OF VIRTUAL REALITY IN LEARNING ENGLISH - Mamayusupova Nargiza Kamol qizi; Ochilova Noila Farmonovna (Journal of new century innovations, 2023)
Pedagogy is enriched with new types of training sessions, which are possible with the development of virtual reality technology. The usual trappings in distance learning and blended learning are complemented by interactive audio-video online sessions. As theoretical methods become more thoroughly explored, there is an increasing need to experiment with practical ones. Now we can see what role VR will play in the field of foreign language learning in the future. An analysis of the definition of the concept of virtuality made it possible to identify its main features and capabilities, allowing us to speak of virtual reality as an ideal educational environment.